Analisis Penambahan Serbuk Batu Karang Dan Kapur Terhadap Nilai CBR Dan Permeabilitas Tanah Lempung - Idhang, Andi Adil Batara; Sariman, Syahrul; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Clay is a type of soil that has a low bearing capacity, so it needs to be stabilized to improve its quality as a road foundation. This research aims to analyze the effect of the addition of coral powder and lime on the value of California Bearing Ratio (CBR) and permeability of clay soil. The research was conducted in the laboratory using a mixture variation of 5% coral powder and lime with variations of 5%, 10%, and 15%. Tests were carried out on soil mechanical properties, especially CBR and permeability tests. The results showed that the addition of coral stone powder and lime increased the CBR value and decreased the permeability coefficient of clay soil. The highest CBR value was obtained in a mixture of 5% coral powder and 15% lime, with a significant increase compared to the original soil. The novelty of this research lies in the use of coral powder as a soil stabilization material combined with lime, which proved effective in increasing the strength of clay soil. The results of this study can be applied to road construction projects in areas with less stable clay soil characteristics. from this study it is concluded that the combination of coral powder and lime can increase soil bearing capacity and decrease permeability, making it suitable for use in soil stabilization in infrastructure projects.